2022
DOI: 10.2138/am-2022-8039
|View full text |Cite
|
Sign up to set email alerts
|

3D crystal size distributions of pyroxene nanolites from nano X-ray computed tomography: Improved correction of crystal size distributions from CSDCorrections for magma ascent dynamics in conduits

Abstract: This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America.The published version is subject to change. Cite as Authors (Year) Title. American Mineralogist, in press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…DOI: https://doi.org/10.2138/am-2022-8765. http://www.minsocam.org/ from pyroclasts reflect temporal changes in the balance between nucleation and growth during magmatic processes (e.g., Cashman and Marsh 1988;Marsh 1998;Armienti 2008;Mujin et al 2017;Okumura et al 2022a).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…DOI: https://doi.org/10.2138/am-2022-8765. http://www.minsocam.org/ from pyroclasts reflect temporal changes in the balance between nucleation and growth during magmatic processes (e.g., Cashman and Marsh 1988;Marsh 1998;Armienti 2008;Mujin et al 2017;Okumura et al 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the large variations in syneruptive crystal growth rates (e.g., Couch et al 2003;Brugger and Hammer 2010b;Befus and Andrews 2018) also can affect the resultant CSD and render its interpretation difficult. For example, Okumura et al (2022a) showed that slow crystallization (both nucleation and growth) can result in a CSD slope similar to that of rapid crystallization by using the formulas of Marsh (1998). As a measure against this, a new expression of CSDs proposed by Okumura et al (2022a) reduces the effects of variable growth rates by adopting 3D short-axis length instead of 3D long-axis length as crystal size.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations